Intention to Use Blockchain Technology (BCT) among Last-mile Logistics in Johor, Malaysia - Leong Wen Wen,; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2023)
Global e-commerce growth has caused the logistics industry to transform. The customers specifically expect door-to-door, same-day or next-day delivery services for home deliveries. Lack of capacity of logistics industry had let the companies difficult to meet the customer demand. However, the adoption of Blockchain technology is still in its early stages among the logistics sectors in the Malaysia. The aim of this study is to identify the level of intention to use blockchain technology and to determine the relationship between three independent variables which are Relative advantage, Top management support, Government Support and intention to adopt blockchain technology intention. Technology Organization Environment theory was used in this study. A number of 45 respondents were included in the questionnaire analysis from the Last-mile Logistics companies. Based on the analysis and findings it showed that organizations will likely to adopt blockchain technology while it is better than existing technology. Besides, top management plays a role for decision making and allocates resources for blockchain technology adoption. The government support can drive the organization to research and development the new technology.